EFEKTIFITAS LEMBAGA ADAT DALAM RANGKA PELESTARIAN HUTAN GUNUNG KIYANGAN DESA REMBITAN KECAMATAN PUJUT KABUPATEN LOMBOK TENGAH - Abdul Rahman; Riani Bakri (Jurnal Pallangga Praja (JPP), 2020)
In an effort to save and preserve forests, one of the efforts made by the Central Lombok District Government is to strengthen the direct involvement of local communities. An example is the Traditional Institution of Kiyangan Forest Management in Rembitan Village, which needs to be tested for effectiveness. This type of research is a qualitative research with an inductive approach. Data analysis techniques were carried out using the principles of triangulation. In conclusion: efforts to save and preserve the Gunung Kiyangan forest with the help of the Gunung Kiyangan Forest Management Customary Institution have proven to be effective.